Pengaruh Faktor Fraud Hexagon Terhadap Kecurangan Laporan Keuangan Pada Sektor Consumer Non – Cyclicals - Nur Fahmi Kusuma Aji (Edunomics Journal, 2025)
Fraud refers to intentional dishonesty, misrepresentation in presenting company assets, or manipulated financial data that benefits the manipulator. Misstatements by employees are made by recording fictitious revenue, reducing expenses, or inflating income. Fraud is typically committed to cover up poor company performance. The purpose of this study is to examine the impact of external pressure, nature of the industry, auditor changes, director changes, CEO duality, and political connections on fraudulent financial reporting. This study is a quantitative research using secondary data. Secondary data is obtained from the annual reports and financial statements of consumer goods sector manufacturing companies listed on the Indonesia Stock Exchange. The objects of this study are Consumer Non-Cyclicals sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2020-2022. The sample is determined using a purposive sampling method. In data analysis, the researcher employs stages of descriptive statistical tests, hypothesis testing, and multiple linear regression analysis with the help of Microsoft Excel and STATA software. The results show that the external pressure variable, proxied by leverage, has no impact on fraudulent financial reporting. The nature of the industry variable, proxied by receivables, has no impact on fraudulent financial reporting. The change in auditor variable, proxied by TACC, does not have a significant negative impact on fraudulent financial reporting. The director changes variable, proxied by BDOUT, has no impact on fraudulent financial reporting. The CEO duality variable has no impact on fraudulent financial reporting. The collusion variable, proxied by political connections, has an impact on fraudulent financial reporting.